HUBUNGAN FAKTOR MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PERAWAT RUANG RAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) PETALA BUMI PEKANBARU - Nur Maimun; Fina Aryani (LPPM Universitas Abdurrab, 2016)
Productivity is very important in determining the continuity of the company or organization. Besides labor productivity is also influenced by motivation, workload, and work environment. Motivates one employee to work usually is complicated, because it involves many factors of motivation. Motivation as a psychological process in a person influenced several factors such as internal and external factors. The purpose of this study was Relationships Work Motivation Factor Against Nurses Work Productivity patient inpatient in RSUD Petala Bumi. This type of research is quantitative by using a cross sectional study design with total sampling technique. The results of research that there is a connection between the personal maturity (p value = 0.000), there is a relationship between desire and expectation (p value = 0.000), there is a relationship between needs (p value = 0.007), there is a relationship between job satisfaction (p value = 0.005 ), there is a correlation between the work environment (p value = 0.005), there is a correlation between salary (p value = 0.000), there is a relationship between the award (p value = 0.005) with productivity, and there is no relationship between control and productivity (p value = 0.311). Then advice is to improve personal maturity employees , meet wishes and expectations employees and the need for example by the award for employees with performance to work created satisfaction that may increase productivity work..